Chemical analysis of archaeological metals found in a Roman burial site in Castro del Río (Córdoba, Spain) - Daniel Cosano; Dolores Esquivel; Carmen de Tena; José Rafael Ruiz Arrebola (Next Materials)
Corrosion is a phenomenon that affects many metals, especially if they are buried for long periods of time, as often happens with many metallic archaeological artifacts. In a Roman tomb excavated in the locality of Castro del Río, on the southern Iberian Peninsula, the remains of two metal sheets were found along with objects belonging to the funerary ensemble. These sheets are currently preserved in the Archaeological and Ethnological Museum of Córdoba. One of the sheets was made of lead and appeared to be in a good state of preservation. The other, made of tin, lead and copper layers, showed obvious signs of corrosion. Following this study conducted using various instrumental techniques, such as X-ray fluorescence spectroscopy, X-ray diffraction, Raman microscopy and scanning electron microscopy with energy-dispersive X-ray spectroscopy analysis, it was determined that, as mentioned earlier, the composition of the first sheet was lead-based and the second sheet was composed of five layers of metal. Of these five layers, the central one was made of tin, which was sandwiched by two lead layers, and finally two copper layers covered these. The different chemical compounds forming the corrosion layers were also identified. These results will enable the conservators/restorers at the Archaeological and Ethnological Museum of Córdoba to establish appropriate conservation guidelines for both materials.